Memorandum on home treatment service
1940-12-17 1940 1940s 4 pages Allowances would be made in respect of (a) special costs such as those involved in rural practice, (b) for the purchase of particular instruments, etc., (c) use of the practitioner's house for practice purposes — mostly in rural areas, in urban areas practice will be conducted from a central clinic at which messages would be received, records kept, etc., (d) travelling and mileage. 8. REPRESENTATION OF PRACTITIONERS Professional Committees analogous to the existing Panel Committees will be set up to represent the medical staff, and to deal with such disciplinary, scientific, or other matters as may be referred to them. 292/847/1/23